Triamcinolone Acetonide Oromucoadhesive Paste for Treatment of Aphthous Stomatitis - Hamed Hamishehkar; Ali Nokhodchi; Saeed Ghanbarzadeh; Maryam Kouhsoltani (Advanced Pharmaceutical Bulletin, 2015)
Purpose: The aim of this study was to prepare the optimized oral paste formulation of Triamcinolone acetonide intended to be used in aphtous stomatitis. Methods: Plastibases were prepared using mineral oil and polyethylene (95:5). Oral paste formulations were prepared with different mixtures of three hydrocolloids solids, including gelatin, pectin and sodium carboxymethylcellulose, with different ratios, as well as Plastibase. Long-term and short-term stability of prepared formulations were studied in the case of color and consistency of pastes. Franz diffusion cell and dialysis membrane were employed for release study. Release data were fitted in the kinetic models to find out the mechanism of drug release. Results: Formulation containing 60% plastibase, 3.3% pectin, 6.6% gelatin and 30% carboxymethylcellulose showed desired durability of adhesion, spreadability and rheology property in healthy volunteers and was compared with reference formulation (Adcortyl®) in the case of release profile. Although, optimized formulation and Adcortyl followed the Higuchi and first order release kinetics respectively, optimized formulation showed similar release profile to reference formulation. Conclusion: Optimized oral paste formulation of Triamcinolone Acetonide showed similar characteristics with reference formulation and could be used as an effective drug delivery system for the treatment of recurrent aphthous stomatitis.